COMPREHENSIVE MIDWIFERY CARE IN NY “F” WITH NORMAL PREGNANCY AT THE HEALTH CENTER TANETE BULUKUMPA DISTRICT BULUKUMBA DISTRICT SEPTEMBER - DECEMBER PERIOD YEAR 2024 - Sri Eka Juniarli; Nabila (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Pregnancy, childbirth and postpartum are normal processes. However, you must be careful about this situation so that it does not become a complication. Complications that often occur in pregnant women are anemia, chronic energy deficiency (CED), bleeding, hypertension that continues during childbirth, postpartum, and family planning services. Therefore, efforts are made to provide comprehensive midwifery care. The aim is to provide comprehensive care to Mrs